Exposure of medical students to pharmaceutical marketing in primary care settings: frequent and influential - SARIKAYA, ÖZLEM (SPRINGER, 2009)
It is known that interaction between pharmaceutical companies and medical professionals may lead to corruption of professional values, irrational use of medicine, and negative effects on the patient-physician relationship. Medical students frequently interact with pharmaceutical company representatives and increasingly accept their gifts. Considering the move toward early clinical encounters and community-based education, which expose students early to pharmaceutical representatives, the influence of those gifts is becoming a matter of concern. This study examines the frequency and influence of student exposure to drug marketing in primary care settings, as well as student perceptions of physician-pharmaceutical company relationships. This was a two-phase study consisting of qualitative research followed by a cross-sectional survey. Clinical experience logbooks of 280 second-year students in one school were analysed, and the themes that emerged were used to develop a survey that was administered to 308 third-year students from two medical schools. Survey results showed a 91.2% exposure to any type of marketing, and 56.8% of students were exposed to all classes of marketing methods studied. Deliberate targeting of students by pharmaceutical representatives, in particular, was correlated with being less sensitive to the negative effects of and having positive opinions about interactions with pharmaceutical companies. The vast majority of students are exposed to drug marketing in primary care settings, and may become more vulnerable to that strategy. Considering that medical students are vulnerable and are targeted deliberately by pharmaceutical companies, interventions aimed at developing skills in the rational use of medicines and in strategies for coping with drug marketing should be devised.
Keywords: Drug industry relationships; Conflict of interest; Pharmaceutical representatives; Marketing methods; Primary health care settings; NATIONAL-SURVEY; INDUSTRY; ATTITUDES; EDUCATION; PHYSICIANS; PROMOTION; PHARMACOTHERAPY; EXPERIENCE; IMPACT